'Progressive MS – macro views': The need for novel clinical trial paradigms to enable drug development for progressive MS. (October 2017) - Zaratin, P; Comi, G; Leppert, D
This article outlines the principal challenges to establish a standard phase-2 approach for progressive multiple sclerosis (PMS) and presents referring strategies to accelerate the registration process via a guidance approved by regulatory agencies. Accordingly, the contribution of 'big datasets' for a better understanding of the natural history of primary-progressive multiple sclerosis (PPMS) and secondary-progressive multiple sclerosis (SPMS) and of their prognostic factors and the value of novel biomarkers are discussed. The establishment of new industry–academic initiatives, such as independent consortia under the umbrella of Progressive MS Alliance (PMSA), with the endorsement of MS organizations and Scientific Societies (e.g. European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS)) may be crucial to overcome some of the current challenges. Within this frame, the continuous interaction with regulatory agencies is instrumental for the formal validation of the many developments suitable to improve clinical trialling in PMS.